Una propuesta de programación práctica de español para extranjeros (a1, a2) en el contexto de programas educativos en Extremadura - PÉREZ PAREJO, Ramón (Didáctica. Lengua y Literatura, 2010)
In the frame of the different agreements and statements signed by the Ministry of Education and the Ministry of Social Welfare with the autonomous communities in order to promote a higher and better attention to those students under unfavorable conditions, the Education Authorities in Extremadura are carrying out two programs at the moment, the Reinforcement, Counseling and Support Plan (P.R.O.A. in Spanish) and the Educational Support for Immigrant Students and Adult Immigrants. In this study we present and analyze a course program of Spanish for Foreigners followed in the two plans mentioned. The course has been held at “Zurbaran” Secondary School in Badajoz, taking the most important documents of the didactics of Spanish as a Second Language as theoretical references and adapting them to the real situation of the immigrant students who have taken part in both programs.
Keywords: Spanish for Foreigners; Didactics; Curriculum design; Reinforcement and Support plans